Gold(III)-catalyzed synthesis of 2, 5-disubstituted furans from substituted 5-methoxyhex-3-yn-2-ols—Mechanistic outlook. Issue 20 (18th October 2021) - Behera, Sagarika; Bera, Nabakumar; Sarkar, Debayan
Abstract: Gold(III)-catalyzed activation of alkynes has been applied for the synthesis of 2, 5-disubstituted furans from substituted 5-methoxy-hex-3-yn-2-ols. Mechanistically, the reaction proceeds via an allenyl carbocation intermediate followed by 5-endo-dig cyclization. The high-yielding, open-air, room temperature reaction conditions applied to synthesize a series of alkyl, aryl, and hetero aryl-substituted furans provide uniqueness to the strategy. Graphical Abstract: UF0001